Near 100% ethene selectivity achieved by tailoring dual active sites to isolate dehydrogenation and oxidation - Chaojie Wang (Nature Portfolio, 2021)
It is important but challenging to prohibit deep oxidation of alkene in oxidative dehydrogenation of light alkane. Here, dual active sites are tailored to isolate dehydrogenation and oxidation thus achieving superior ethene selectivity.